The assessment of sarcopenia using psoas muscle thickness per height is not predictive of post-operative complications in IBD. (3rd October 2021) - Alipour, Omeed; Lee, Vivian; Tejura, Tapas K.; Wilson, Melissa Lee; Memel, Zoe; Cho, Jaehoon; Cologne, Kyle; Hwang, Caroline; Shao, Ling
Abstract: Background: Sarcopenia is associated with postoperative complications in inflammatory bowel disease. It has most commonly been defined using the skeletal muscle index, computed after analysis of cross-sectional muscle area at L3. Psoas muscle thickness normalized to height (PMTH), which is easier to derive, is a potential surrogate of SMI and sarcopenia in patients with cirrhosis and chronic pancreatitis. We investigate whether sarcopenia defined by PMTH has utility in predicting post-operative outcomes in patients with inflammatory bowel disease. Methods: We performed a retrospective study of adults undergoing IBD-related surgery from 2009 to 2019 at two hospitals. Sarcopenia was defined by sex-specific PMTH at the umbilicus on cross-sectional imaging using a 50 th percentile median cutoff. Predictive models were created using variables (BMI, age, sex, smoking status, albumin, INR, platelets, hemoglobin, hypertension, diabetes, CAD, medications) that may be associated with complications (mortality, reoperation, readmission, transfusions, ICU admission, infection, DVT/PE), and sarcopenia for comparison. Results: 85 patients with IBD were included. Lower albumin level (OR = 0.52, p  = 0.039) and biologic use (OR = 5.92, p  = 0.006) were associated with postoperative complications. There was no significant difference using PMTH compared to a model incorporating hypoalbuminemia and biologic use in predicting complications. Sarcopenia on univariate analysis was associated with a lower 30 day rate of reoperation ( p  = 0.04). Conclusions: A low status of PMTH was not associated with increased postoperative complications, however hypoalbuminemia and biologic use were. PMTH as a surrogate for sarcopenia requires further study, ideally with prospective studies comparing PMTH with accepted radiographic surrogates for sarcopenia, to determine its role in clinical decision making.